Introducing a particular mathematical model for predicting the resistance and performance of prismatic planing hulls in calm water by means of total pressure distribution (Journal of Naval Architecture and Marine Engineering, 2015)
Mathematical modeling of planing hulls and determination of their characteristics are the most important subjects in hydrodynamic study of planing vessels. In this paper, a new mathematical model has been developed based on pressure distribution. This model has been provided for two different situations: (1) for a situation in which all forces pass through the center of gravity and (2) for a situation in which forces don not necessarily pass through the center of gravity. Two algorithms have been designed for the governing equations. Computational results have been presented in the form of trim angle, total pressure, hydrodynamic and hydrostatic lift coefficients, spray apex and total resistance which includes frictional, spray and induced resistances. Accuracy of the model has been verified by comparing the numerical findings against the results of Savitsky's method and available experimental data. Good accuracy is displayed. Furthermore, effects of deadrise angle on trim angle of the craft, position of spray apex and resistance have been investigated.